2016
DOI: 10.1371/journal.pone.0166236
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism and Its Complicated Relationship with Tumor Growth and Perfusion in Head and Neck Squamous Cell Carcinoma

Abstract: ObjectiveTo determine the relationship between tumor glucose metabolism and tumor blood flow (TBF) in head and neck squamous cell carcinoma (HNSCC).MethodsWe retrospectively analyzed 57 HNSCC patients. Tumor glucose metabolism was assessed by maximum and mean standardized uptake values (SUVmax and SUVmean) obtained by 18F-fluorodeoxyglucose positron-emission tomography. TBF values were obtained by arterial spin labeling with 3-tesla MRI. The correlations between both SUVs and TBF were assessed in the total ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Insufficient blood supply leads to relatively low TBF, whereas an aggressive tumor itself demands a high glucose uptake in anaerobic glycolysis. The uncoupling of blood supply and tumor growth may result in low oxygenation of tumor tissue, i.e., tumor hypoxia, which might lead to resistance to radiotherapy (26). Our study showed no correlation between the SUVmax of primary tumors or metastasis lymph nodes and radiation response.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Insufficient blood supply leads to relatively low TBF, whereas an aggressive tumor itself demands a high glucose uptake in anaerobic glycolysis. The uncoupling of blood supply and tumor growth may result in low oxygenation of tumor tissue, i.e., tumor hypoxia, which might lead to resistance to radiotherapy (26). Our study showed no correlation between the SUVmax of primary tumors or metastasis lymph nodes and radiation response.…”
Section: Discussioncontrasting
confidence: 67%
“…Komar G previously concluded that there was no correlation between SUV and TBF value in HNSCC patients (25), our study came to a similar conclusion. Fujima (26) showed significant correlations between SUV and TBF in HNSCC by different T-stage and tumor locations, i.e., positive correlation in the early T-stage pharynx/oral carcinoma, negative correlation in the advanced T-stage in both the pharynx/oral and sinonasal carcinoma, and no correlation in the overall patient analysis. The conflicting result may be due to several factors such as tumor size, tumor proliferation activity, or the mismatch of angiogenesis and tumor proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…FDG-PET/CT data provide rough anatomical information about the tumor revealed by the lesion's elevated FDG uptake. Moreover, the tumor margin can be easily set using the threshold of FDG uptake from FDG-PET/CT imaging, allowing objective quantification of the whole tumor area (13). From this morphological data, several parameters related to the tumor morphological shape can be calculated.…”
Section: Introductionmentioning
confidence: 99%
“…We measured the SUV value for each tumour by determining the automated ROI using an isocontour threshold method. A threshold SUV value of 2.5 was set for the tumour ROI delineation to exclude the central necrosis or nearly normal tissue uptake [16]. If a tumour extended to two or more slices, all slices that showed tumour FDG uptake were analyzed.…”
Section: Image Analysismentioning
confidence: 99%